Development and Implementation of a Thunkable-Based Android Mobile Learning Application for Computer Hardware Instruction in a Vocational High School - Muhammad Ali Zainal Abidin; Firman Jaya; Rahmad Shofan Razaqi (Tinta Emas Publisher, 2026)
Digital learning in vocational education requires media that can visualise technical concepts while supporting independent access beyond classroom time. This study developed and implemented a Thunkable-based Android mobile learning application for the Informatics topic of computer hardware and its functions at State Vocational School 1 Kendit, Indonesia. The study adopted a research-and-development design using the ADDIE stages of analysis, design, development, implementation, and evaluation. The product included learning objectives, a material guide, hardware illustrations, instructional content, an interactive quiz, and automated evaluation. Feasibility was examined through content validation by a subject-matter expert, media validation by an instructional-media expert, and user-response questionnaires completed by 25 Grade X Computer and Network Engineering students. The material validation score was 84.0%, indicating a very feasible category, while media validation reached 80.6%, also indicating a very feasible category. Student responses were substantially higher at 92.7%, with the strongest item being ease of understanding the hardware material (94.4%). The findings show that a low-code Android application can provide a practical, visually supported, and flexible learning medium for vocational hardware instruction. However, the evidence should be interpreted as feasibility and perceived usability rather than causal proof of learning gains because the study did not employ a controlled pre-test-post-test design. The study contributes a context-specific mobile learning model for vocational informatics instruction and offers a replicable development pathway for teachers seeking to transform students' smartphone use into structured learning activity.